Types of anti-detonation devices and the mechanism of their effect on automobile gasoline (Texas Journal of Engineering and Technology, 2026)
Today, a cycle with external mixture formation (gas-diesel cycle) has been developed in which diesel engines are combined with natural gas. Almost all gasoline engines have switched to direct injection into the engine's combustion chamber. Gasoline engines today use not only gasoline, but also natural compressed or compressed petroleum gases, alcohols and alcohol-gasoline mixtures